ヒガシ ナンキョク タイリク ニシ ヤマト ヌナタクス ノ チシツ - 白石, 和行; シライシ, カズユキ; SHIRAISHI, Kazuyuki (国立極地研究所, 1975)
P(論文) 第14次南極越冬隊の内陸調査隊は,1973年12月にやまと山脈南西方30kmにある,7つのヌナタク群を踏査した.このヌナタク群はおのおの300～1,000mの広がりをもつが,大部分はモレーン堆積物でおおわれている.最高峰は2,282mで,氷床からの比高は150m にすぎない.当地域にみられる岩石は,やまと山脈のものと類似しているが,チャーノッカイト類は認められない.最北端のヌナタクは,普通角閃石黒雲母片麻岩からなり,他のヌナタクは花尚岩質片麻岩類が広く分布する.変塩基性岩,花崗岩質岩脈,ペグマタイトは,全地域にみられる.岩石の産状およびこの地域の構造的特徴から,当地域の地質は,ベルジカ山脈の地質と密接に関係しているものと思われる. Seven nunataks, provisionally named the West Yamato Nunataks, located at 30 km southwest of A group of the Yamato Mountains were briefly investigated by the present author in 1973. The heighest peak is 2,282m above sea level but the relative height from the ice surface is only 150m. The rocks exposed in the nunataks are similar to those of the Yamato Mountains except the fact that no charnockitic rocks are found. Hornblendebiotite gneiss is developed in the northernmost nunatak, while granitic gneiss is distributed in the other nunataks. Metabasites, granitic dykes and pegmatites occur throughout the whole area. The occurrences of these gneisses as well as the structural characteristics may suggest a close geological relation between this area and the Belgica Mountains located about 150 km southwest of these nunataks. departmental bulletin paper